Management of Stable Angina with Ivabradine as Safe Alternative to Patients with Myasthenia Gravis - Giuliano Ohde Dalledone; Gustavo Lenci Marques; Renata Dal-Prá Ducci; Arnaldo Laffitte Stier Junior; Cláudia Suemi Kamoi Kay; Lineu Cesar Werneck; Paulo José Lorenzoni; Rosana Herminia Scola (Case Reports in Neurological Medicine)
Management of cardiac symptoms in myasthenia gravis (MG) patients can be challenging. The aim of this report is to describe the safe use of ivabradine for stable angina in MG patients. A 48 y.o. woman, with MG diagnosis, presented stable angina. Therapies choices were reduced considering concomitant disease as well as previous and unsuccessful cardiologic managements. Ivabradine showed unexpected results. The patient presented an improvement of neurological and cardiac symptoms, bringing ivabradine as one more therapeutic option to similar patients. In this report we recommend ivabradine as an effective and safe drug for treatment of stable angina in MG patients.